Intervention research partnerships: enablers for activating health in all policies approach?. (13th November 2019) - Porcherie, M; Bader, C; Faure, E; Roué le Gall, A; Vaillant, Z; Thomas, M F; Rican, S; Héritage, Z; Simos, J; Cantorregi, N
Abstract: Introduction: Action on the determinants of health and equity involves the participation of all sectors, including non-health sectors. Understanding the opportunities and constraints to engage in the complex issue of health inequalities requires opening the black box of policy making. It also requires close interaction between field actors and researchers. This paper will aim to analyze the modalities of collaboration between researchers and field actors in the service of knowledge sharing, within the GREENH-City project. Methods: The GREENH-City project was built in an interdisciplinary and intersectoral manner and involves close collaboration with the WHO French Healthy Cities Network (FHCN). Its objective is to characterize the most promising health interventions in all policies at the city level to promote equity through green space policies. Based on the knowledge sharing model and the theory of diffusion of innovations, we will analyze how this research allows initiating collaborations between the different municipal sectors on health issues. Results: The intervention nature of the project seems to help the dissemination of collaborations, particularly between health services and green space services within the cities of the FHCN. The analysis, using theoretical models, of the body of empirical data collected from cities will make it possible to identify the levers and collateral effects activated by the research project. Discussion: The GREENH-City project was built on the basis of an interventional research framework. This choice was made precisely because of the interaction it induces between researchers and practice environments. Initial empirical results suggest that it promotes the dissemination of knowledge, a necessary first step in the evolution of practices. Indeed, the effective appropriation of research results can only be assessed in the long term and must take into account the contextual elements specific to each FHCN involved in the research. Key messages: Implementation of interventional research helps to engage fields collaborations. Health in all policies may be supported by a research project at the local level.